2009
DOI: 10.1152/ajprenal.00247.2009
|View full text |Cite
|
Sign up to set email alerts
|

Long-term therapeutic effect of vitamin D analog doxercalciferol on diabetic nephropathy: strong synergism with AT1 receptor antagonist

Abstract: The intrarenal renin-angiotensin system (RAS) plays a key role in the development of diabetic nephropathy. Recently, we showed that combination therapy with an AT 1 receptor blocker (ARB) and an activated vitamin D analog produced excellent synergistic effects against diabetic nephropathy, as a result of blockade of the ARB-induced compensatory renin increase. Given the diversity of vitamin D analogs, here we used a pro-drug vitamin D analog, doxercalciferol (1␣-hydroxyvitamin D 2), to further test the efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 48 publications
4
92
1
Order By: Relevance
“…The purified 4.1 kb PmeI DNA construct ( Figure 1A) was microinjected into fertilized embryos isolated from pregnant female DBA/2J mice, a genetic background known to be susceptible to diabetic renal injury. 14,16,22 PCR-based genotyping identified 3 positive pups of 62 born from the microinjection, and cross of these founder lines with DBA/2J mice resulted in germline transmission in lines 5 and 12. This study focused on line 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purified 4.1 kb PmeI DNA construct ( Figure 1A) was microinjected into fertilized embryos isolated from pregnant female DBA/2J mice, a genetic background known to be susceptible to diabetic renal injury. 14,16,22 PCR-based genotyping identified 3 positive pups of 62 born from the microinjection, and cross of these founder lines with DBA/2J mice resulted in germline transmission in lines 5 and 12. This study focused on line 5.…”
Section: Resultsmentioning
confidence: 99%
“…13 We reported that vitamin D analog therapy reduced albuminuria and prevented podocyte loss in experimental models of type 1 and type 2 diabetes. [14][15][16] We also showed that podocytes express the vitamin D receptor (VDR) that is highly inducible by 1,25(OH) 2 D 3 , 17 1,25(OH) 2 D 3 transcriptionally stimulated the expression of nephrin, a key slit diaphragm protein synthesized by podocytes, 18 and deletion of VDR in mice led to early onset and robust albuminuria in diabetic state. 19 Together these data suggest that podocytes may be a key antiproteinuric target of vitamin D 20 ; however, no study has directly addressed the renoprotective role of podocyte VDR signaling.…”
mentioning
confidence: 97%
“…Experimental studies have shown that VDR knockout mice have higher expression of renin, angiotensin, and angiotensin receptors under diabetic conditions and may develop severe renal injury resulting in early onset albuminuria, glomerulosclerosis, and interstitial fibrosis mainly due to local RAAS activation. Vitamin D exerts anti-inflammatory effects by modulating antigen-presenting cells' function, reducing expression of cytokine interleukin-12 (IL-12), and repressing transcription of genes encoding interleukin 2 (IL2) and interferon gamma [42][43][44].…”
Section: Vitamin D/vdrmentioning
confidence: 99%
“…Studies have shown that the increased activity of RAS in local tissue leads to the pathological process of target organs, like fibrosis, 3) oxidative stress 4) and inflammation. 5) Recent studies have shown that such components of RAS as renin, ACE, and Ang II receptors are expressed in the skeleton. 6) Functional studies have revealed that Ang II could stimulate the differentiation and activity of osteoclasts in vivo 7) and in vitro, 8) and that the activation of RAS induced high-turnover osteoporosis with accelerated bone resorption.…”
Section: Involvement Of the Skeletal Renin-angiotensin System In Age-mentioning
confidence: 99%